MASA PANDEMI: UMKM DALAM MENGGUNAKAN SOCIAL MEDIA DAN E-COMMERCE DALAM MEDIA PROMOSI - Devi Permatasari Wijoyo; Marina Wardaya (Jurnal Vicidi, 2021)
Journal of Literature review which contains the condition of MSMEs, especially tailors who have been affected by job losses during the pandemic. Starting from the description of “UMKM”, what are the impacts of the Covid 19 Pandemic felt by MSME entrepreneurs, the need to take online promotional actions through social media, what are the benefits of e-commerce, why is it necessary to move “UMKM” from offline to online shop, and the influence of online stores on trade relations. Keywords : Tailor, Pandemic, Social Media, Online Shop, UMKM, E-commerce, Promotion